Effects of Peppermint Oil Inhalation on Vertical Jump Performance in Elite Young Professional Soccer Players: A Double-Blinded Randomized Crossover Study - Aedo-Munoz, E; Merino-Munoz, P; Brito, C (Elsevier Ltd, 2024)
Aims: To evaluate peppermint essential oil (PEO) inhalation s effect on young soccer athletes motor performance. Methods: A randomized crossover design was used to test the effect of the PEO. Eleven U-17 soccer players were evaluated into two conditions (PEO and Placebo – PLA). The players were tested in squat jump and countermovement jump and inhaled PEO or PLA and 10 min later performed the physical tests again. A mixed ANOVA was performed to test the hypotheses. Results: Main effects were found for the time in jumping height in the CMJ (p = 0.037). No main and interaction effects were found in the SJ variables. Conclusion: From the results, decrease CMJ performance acutely, both conditions presented decrease in JH, but based in effect size, PLA decrease is higher (more sample size for corroborate this) possibly due to improvements in the eccentric yielding sub-phase, where mentioned phase could be reflecting neural changes (required experimental verification). The PEO could be the interest in trainers for use before of match or in the half-time for minimize the decreased of physical performance by the rest. © 2024
Keywords: Aromatherapy; Biomechanics; Football; Kinetics; Nutrition; Physical performance; Physiology